Chi-Square and 2-Way ANOVA for Accounting Students: Analysis of Natural Gas Sales Volume by Pipeline by Customer Type in Indonesia - Suhardjo, Suhardjo; Renaldo, Nicholas; Sevendy, Tandy; Rusgowanto, Fransisca Hanita; Pramesti, I Gusti Ayu Asri (First Ciera Publisher, 2023)
This study aims to analyze the sales volume of natural gas through pipelines based on the type of customer in Indonesia. This research combines two different fields of study, namely accounting and statistical analysis. This research in its early stages will explain the chi-square and 2-way ANOVA analysis according to the data presented. Based on the analysis that has been done, it can be concluded that there are differences in the volume levels of sales of natural gas through pipelines according to the type of customer (household, commercial, industry, power plants, and SPBE/SPBG) and there are not too many differences between the volume levels of natural gas sales through pipelines annually (2010-2017). Based on the findings of this study, it is suggested that the government and gas companies focus on developing pipeline infrastructure to support the growth of the industrial and commercial sectors.